RELATIONSHIP BETWEEN ESTROGEN DEFICIENCY AND PERIODONTAL DISEASE IN POSTMENOPAUSAL WOMEN - Kasimova Edie Valulevna; Muratova Nigora Juraevna; Ochilova Malika Ulmasovna; Rakhimov Bakhtiyor Gafurzhanovich (Journal of new century innovations, 2022)
This article is a review and presents the results of research by foreign scientists on the effects of estrogen deficiency on the oral cavity and their impact on the development of periodontal diseases in women during natural and surgical menopause. The dental status of women aged 35 to 70 years was studied; scientists noted the negative impact of estrogen deficiency on the state of the whole organism,